Responsible firms : CSR, ESG, and global sustainability - Choi, J. Jay; Kim, Jimi (Emerald Publishing Limited, 2024)
The purpose of corporations has long been debated, with the traditional view asserting that a firm's primary responsibility is to maximize shareholder profits. This profit-centric approach is believed to drive efficiency, innovation, and economic growth. However, an evolving perspective argues that corporations have broader responsibilities that include social and environmental considerations, suggesting that corporations should also focus on the well-being of employees, fair wages, and sustainable practices to create positive social impacts and long-term benefits. Responsible Firms: CSR, ESG, and Global Sustainability examines global contemporary models of the "responsible firm", investigating how broader social responsibilities are, or are not, integrated and proposing new concepts and frameworks to improve. International Finance Review publishes theme-oriented volumes on various issues in international finance, such as international business finance, international investment and capital markets, global risk management, international corporate governance and institution, currency markets, emerging market finance, international economic integration, and related issues.
Includes index.
Keywords: Social responsibility of business.; Business & Economics -- Corporate Finance -- General.; Business ethics and social responsibility.; Corporate finance.; elektronické knihy; electronic books